Systems with optimal geometric shapes - A. K. Yusupov; H. M. Musеlеmov; R. I. Vishtalov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. In this paper, buildings of various shapes that have high seismic resistance are considered. Such seismic resistance is provided by the rational shape and outlines of the building itself. Here, the influence of the torsion of the building in the plan is minimized, thereby eliminating large stresses at the ends of the designed building. At the same time, the translational movement of the building in the plan is preserved.Method. By optimizing the shape and shape of buildings for various purposes, high efficiency of the structure is ensured under seismic effects. By comparing the shape and outlines of various buildings, the best variant of their layout is selected.Result. Structural schemes of buildings and structures with high resistance to seismic effects are given. A comparative analysis and recommendation for the design of earthquake-resistant buildings are given. Structural schemes for buildings and structures of various outlines have been developed: round, square, rectangular; constructive schemes of volumetric seismic-resistant structures, pyramidal, conical of various shapes, have been drawn up. Recommendations for the design of earthquake-resistant buildings and structures with optimal geometric shapes are made.Conclusion.The design schemes proposed in the article can be used in the design of earthquake-resistant buildings and structures for various purposes.